2020
DOI: 10.1177/0300060520931313
|View full text |Cite
|
Sign up to set email alerts
|

Association of miR-146a polymorphism rs2910164 and type 2 diabetes risk: a meta-analysis

Abstract: Objective Circulating miR-146a is aberrantly expressed in patients with type 2 diabetes (T2D), probably resulting from gene polymorphisms. However, the role of polymorphism rs2910164 in T2D pathogenesis remains controversial. Thus, we designed a meta-analysis to investigate the association between rs2910164 and T2D. Methods PubMed and Embase were searched for eligible papers in English published through September 2, 2019. Random or fixed effect models were used to determine risk estimates according to heteroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The meta-analysis approach is an important and reliable method for identifying associations between genetic variants and diseases based on the results of multiple studies to improve statistical power ( 46 ). Several recent meta-analyses have reported an association between the miR-146a rs2910164 polymorphism and T2DM risk ( 47 – 50 ). First, the results of these meta-analyses differ.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis approach is an important and reliable method for identifying associations between genetic variants and diseases based on the results of multiple studies to improve statistical power ( 46 ). Several recent meta-analyses have reported an association between the miR-146a rs2910164 polymorphism and T2DM risk ( 47 – 50 ). First, the results of these meta-analyses differ.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the correlation of rs2910164 with T2DM risk was explored by several case-control studies. A meta-analysis suggested an association of rs2910164 in miRNA-146a gene with T2DM risk [29] . However, in that meta-analysis, only 2,069 cases and 1,950 controls were included.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis has suggested that rs2910164 G allele might be associated with risk of T2DM. However, only four case-control studies with 2,069 cases and 1,950 controls were included [29] , which observations might be under-powered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-146a is another important miRNA for diabetic patients. Evidence-based medicine research shows that the expression of circulating miR-146a is abnormal in type 2 diabetes [82]. MiR-146a was downregulated in diabetic patients and obesity.…”
Section: Relationship Between Mirnas and Diabetes Or Associated Complicationsmentioning
confidence: 99%